ANALISIS HUBUNGAN PERPUTARAN PIUTANG TERHADAP LIKUIDITAS PADA PT. INDOFOOD SUKSES MAKMUR. TBK - Suparno (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2020)
Credit sales can affect the level of liquidity of a company, because the results of credit sales will produce trade accounts receivable which are part of current assets and changes in current assets can affect the level of company liquidity due to the repayment of trade accounts, it will increase cash so the company can pay its short-term obligations. This study aims to find out how the relationship Accounts Receivable Turnover on Liquidity is measured by the current ratio. The object of the research is PT. Indofood Sukses Makmur Tbk taken from the financial statements for the period 2013-2017. This study uses a qualitatif method consisting of two variables, namely accounts receivable turnover as independent and liquidity as the dependent variable. The data analysis method used in this study is simple regression analysis and tested by t-test. The test results show that accounts receivable turnover has a significant relationship to liquidity. The results can be seen in R of 0.88, which means that the relationship between accounts receivable turnover and liquidity has a very strong relationship. This result is reinforced by the results of hypothesis testing through the t-test which shows that accounts receivable turnover has a significant relationship to liquidity of 77.44% while the remaining 22.56% is influenced by other factors not examined by the author.